Literature Review on Selection Criteria of Store Location Based on Performance Measures - TURHAN, GÜLDEN (ELSEVIER SCIENCE BV, 2013)
This paper presents the results of a literature review for understanding the selection criteria of store location in the retail context. The review provides overall insight into prior studies that specifically emphasize on factors influencing store performance. Store performance has been evaluated by using various measures such as store sales, market share, retail patronage, store traffic, store profits and so forth in different studies. The intention of the review is to (1) classify the store location-selection criteria, and (2) provide researchers with a theoretical model on which future research on store performance may be oriented. (C) 2013 The Authors. Published by Elsevier Ltd.
Keywords: store location; population; economic factors; competition; saturation level; magnet; store characteristics; RETAIL LOCATION; HIERARCHY PROCESS; MODEL; COMPETITION; DETERMINANTS; ENVIRONMENT; INTERTYPE; PATRONAGE; CHOICE; IMPACT